2012
DOI: 10.1016/j.future.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Independent checkpointing in a heterogeneous grid environment

Abstract: Abstract-The EU-funded XtreemOS project implements an open-source grid operating system based on Linux. In order to provide fault tolerance and migration for grid applications, it integrates a distributed grid-checkpointing service called XtreemGCP. This service is designed to support different checkpointing protocols and to address the underlying gridnode checkpointers (e.g. BLCR, LinuxSSI, OpenVZ, etc.) in a transparent manner through a uniform interface. In this paper, we present the integration of an indep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…There are generally three types of protocols. Coordinated Checkpointing: This protocol requires processes to coordinate the establishment of their checkpoints to form a coherent global state. Independent checkpointing: This protocol avoids the synchronization phase by allowing each process to save its local state Independently of the others. The advantage of this type of checkpointing is that the overhead is reduced and it can be controlled. Checkpointing induced by communication: In this protocol, the processes take two kinds of checkpoints, local and forced .…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…There are generally three types of protocols. Coordinated Checkpointing: This protocol requires processes to coordinate the establishment of their checkpoints to form a coherent global state. Independent checkpointing: This protocol avoids the synchronization phase by allowing each process to save its local state Independently of the others. The advantage of this type of checkpointing is that the overhead is reduced and it can be controlled. Checkpointing induced by communication: In this protocol, the processes take two kinds of checkpoints, local and forced .…”
Section: Related Workmentioning
confidence: 99%
“…• Independent checkpointing 5,8,9 : This protocol avoids the synchronization phase by allowing each process to save its local state Independently of the others. The advantage of this type of checkpointing is that the overhead is reduced and it can be controlled.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Kovcs et al [32] described the TotalCheckpoint tool, which integrate library-level checkpointer with the application, for software-heterogeneous ClusterGrid infrastructures. Feller et al [33] designed and implemented an extended version of the XtreemOS grid checkpointer, which supports the independent checkpointing protocol. And their results showed that independent checkpointing is more suited than coordinated checkpointing in a heterogeneous grid environment.…”
Section: Related Workmentioning
confidence: 99%